2022
DOI: 10.1136/bmjopen-2022-063302
|View full text |Cite
|
Sign up to set email alerts
|

Police officers’ work–life balance, job satisfaction and quality of life: longitudinal effects after changing the shift schedule

Abstract: ObjectivesTo evaluate mental health-related outcomes of police officers 5.5 years after implementing a new alternating shift schedule which was supposed to improve their health and work–life balance.DesignPre–post study design with a baseline survey at the beginning of the piloting of the new shift schedule in 2015 and another survey 5.5 years later in 2020.SettingPolice departments of a German metropolitan police force piloting the new shift schedule.Participants116 shift-working police officers out of a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
1
2
0
1
Order By: Relevance
“…In a similar study, conducted with state police officers in Spain, there were almost twice as many employees with a university degree, compared to employees from our study but no significant relationships were found between educational level and burnout in this study ( 29 ). According to our results, risk of appearance of job burnout decreased with the increase in academic qualifications, which is consistent with the results from the literature ( 14 , 28 , 31 , 48 ). In EU countries, there are significantly more employees in private security sector with higher education and university degrees ( 12 , 13 , 33 , 49–51 ) than in Serbia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a similar study, conducted with state police officers in Spain, there were almost twice as many employees with a university degree, compared to employees from our study but no significant relationships were found between educational level and burnout in this study ( 29 ). According to our results, risk of appearance of job burnout decreased with the increase in academic qualifications, which is consistent with the results from the literature ( 14 , 28 , 31 , 48 ). In EU countries, there are significantly more employees in private security sector with higher education and university degrees ( 12 , 13 , 33 , 49–51 ) than in Serbia.…”
Section: Discussionsupporting
confidence: 93%
“…However, significant interactions were not revealed ( 55 ). Other studies have found no significant sex differences concerning police officers’ quality of life ( 48–51 , 56 , 57 ). However, research on police officers’ quality of life is only recently emerging ( 50–52 , 58 ).…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, most of the interviewed participants had their homes outside the Kathmandu Valley, making it difficult for them to spend time with their families and loved ones leading to minimal emotional and familial support. On the other hand, police officers' indispensable shift work predicts work-family conflict and mediates between police officers' workload and job stress as well as job dissatisfaction [24][25][26][27]. Generally, police personnel are considered strong, both mentally and physically, and emotionally stable.…”
Section: Discussionmentioning
confidence: 99%
“…De la misma forma, Maslach (1976) en el congreso de la Sociedad Americana de Psicología (APA), propuso a la comunidad científica que el Síndrome de Burnout es "un estrés crónico producido por el contacto con los clientes que conlleva a la extenuación y al distanciamiento emocional en el trabajo". En tal sentido, los trabajadores que lo padecen pueden desarrollar sentimientos de cinismo y desapego por el trabajo, sensación de ineficacia y falta de logros, que afectaban tanto a la organización como al ámbito familiar y personal (Rohwer et al, 2022). En las personas, puede causar problemas de: ansiedad, impotencia, irritabilidad, sentimientos de perturbación, apatía, comportamientos agresivos, adicción al alcohol, problemas familiares, y trastornos fisiológicos como: problemas cardiovasculares, del sistema inmunológico, sexuales, musculares o digestivos.…”
Section: Introductionunclassified